(untitled) (Eurasian Journal of Humanities and Social Sciences, 2025)
In this article, the importance of modern educational technologies in the field of education, in particular, in the teaching of the Uzbek language, the formation of the necessary skills, creative and technological culture for the effective organization of the pedagogical process in the conditions of information age specific for the teacher of modern Uzbek language and literature.